Marking otoliths of Baltic cod (\textitGadus morhua Linnaeus, 1758) with tetracycline and strontium chloride - Stoetera, Sven; Degen-Smyrek, Aisha Karim; Krumme, Uwe; Stepputtis, Daniel; Bauer, Robert; Limmer, Bente; Hammer, Cornelius (Journal of Applied Ichthyology, 2019)
Place: 111 RIVER ST, HOBOKEN 07030-5774, NJ USA Publisher: WILEY Type: Article Identified were suitable dosages of tetracycline hydrochloride (TET) in three single treatments and three combined treatments of TET with 2 mg/kg strontium chloride (STR) in wild western Baltic cod (Gadus morhua), in terms of (a) obtainable mark qualities (visibility of fluorescent bands), (b) growth assessment, and (c) induced mortality rates. Isotonic NaCl solution was injected in a control group (25 cod per treatment). The results provide the basis for imperative age validation studies of Baltic Sea cod. Cod originating from pound nets near Fehmarn Island were kept in swimming net cages at the harbor of Warnemunde for 1.5 months. Mean initial total length was 28(+/- 3) cm (salinity: 13, water temperature: 13 to 8 degrees C). Overall average growth of surviving cod was 0.8 mm/day. In single TET treatments, lowest mortality rates and best mark quality were observed for TET concentrations of 100 compared to 50 and 25 mg/kg wet mass. Mortality rates of the 100 mg/kg treatment group were remarkably lower than in the control group emphasizing the antibiotic effect of TET. By contrast, the double treatment in the TET-STR groups resulted in a binding interaction between both markers in the fish body causing either the antibiotic potency being inhibited or TET and STR forming a non-beneficial chelate (increased mortality), and decreased incorporation of TET in the otolith (reduced visibility of TET bands). Consequently, TET (short-term marker) and STR (long-term marker) should not be injected together. Our results demonstrate that the binding interactions between these substances known from homoiotherm animals also apply for poikilotherms such as fish.